A study of Internet service provider industry stakeholder collaboration in Australia: An institutional perspective. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to examine institutional influences on the customer service (CS) and complaints handling (CH) practices of the Australian Internet industry.Design/methodology/approach – The study adopted a qualitative research methodology using semi‐structured interview as a research method. The study was informed by constructivist/interpretive research paradigm approaches to knowledge. Eleven senior executives from key Internet industry stakeholder organizations were interviewed.Findings – Using the neo‐institutional theory lens, this study found that the institutional forces (regulatory, customer and competition pressures) played a pivotal role in bringing all Internet industry stakeholders together to address CS/CH shortcomings in the old Telecommunications Consumer Protection (TCP) Code 2007. This led to significant changes to the CS/CH practices detailed in the revised TCP Code 2012. The study findings revealed that frequent and fateful collaborations between central institutional actors have led to the emergence of organizational fields. The actors identified in the emerging organizational fields actively influence the CS/CH practices and the subsequent implementation of the practices in vLISPs.Research limitations/implications – The study focused on the functional aspects of service quality (SQ). Technical aspects of SQ is equally important, and future research needs to consider both aspects of SQ when assessing overall performance of vLISPs.Practical implications – The study findings encourage vLISP managers to continue collaboration with external stakeholders and develop customer‐friendly practices that deliver desirable CS/CH outcomes.Social implications – The study findings revealed that when all vLISP industry stakeholders collaborate with each other on a focal issue, there is noticeable progress towards development of CS practices that will contribute to a better CS experience.Originality/value – An evidence‐based approach was used towards understanding and explaining how and why institutional actors of technology‐based service organizations act together. A significant contribution arising from this study is the identification and discussion of emerging organizational fields comprising the central actors in the Internet industry. These emerging organizational fields have the potential to develop into mature organizational fields and inform future CS/CH practices and consumer protection policies in the Australian Internet industry. Acknowledgements : The author thanks all Internet industry participants for their participation in this study. Special thanks to anonymous reviewers for their valuable feedback.